METODE IDENTIFIKASI KERUSAKAN ELEMEN FISIK BANGUNAN HERITAGE DENGAN BUILDING INFORMATION MODELING (BIM) STUDI KASUS ISTANA ALWATZIKHOEBILLAH SAMBAS - Norita Norita; Zairin Zain; Yudi Purnomo (JMARS: Jurnal Mosaik Arsitektur, 2022)
Heritage buildings as architectural heritage assets that describe the identity of a region and the architecture of the past are important to be conserved and maintained. One of the cultural heritage buildings in Indonesia is Alwatzikhoebillah Sambas Palace. This building was built with wood construction. The condition of wood with age will experience changes in characteristics due to its interaction with various factors, especially biological and non-biological factors. Changes in any form cannot be underestimated, so documentation of cultural heritage buildings is needed. One way of documenting cultural heritage buildings is Building Information Modeling (BIM). BIM documentation can record various building information that is inputted in it. This research aim was to mapping and assessing the damage to the physical elements of wood on one of the accompanying buildings on the north side of the Alwatzikhoebillah Palace using BIM. BIM information contains the color code, mapping code, and the extent of the damage that occurs in the 2D view. The variables of this study were limited to biological damage caused by fungi and moss, also non-biological factors due to mechanical, weather, and chemical factors. The results of this research is the wall elements are dominantly damaged caused by wood staining fungus or mechanical erosion and weather changes of 1,64% with the effect of gray stains left on the elements.